Profile of Exon 20 T790M Mutation Incidence Rate with Plasma ctDNA in Lung Adenocarcinoma Patients Receiving EGFR-TKI Treatment - Muhammad Harbi Praditya; Noni Novisari Soeroso; Setia Putra Tarigan; Taufik Ashar; Darren Wan-Teck Lim (Jurnal Respirasi, 2023)
Introduction: Patients with lung adenocarcinoma following epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) treatment will develop acquired resistance after 7 to 16 months of starting the medication, indicated by the emergence of exon 20 T790M mutations. This study aimed to identify the clinical and demographical profile of acquired resistance in patients with lung adenocarcinoma receiving EGFR-TKI therapy through plasma circulating tumor deoxyribonucleic acid (ctDNA) examination. Methods: This was a descriptive study with a retrospective cross-sectional design involving 108 lung adenocarcinoma patients who received EGFR-TKI for more than six months. Exon 20 T790M EGFR mutations were identified as a sign of acquired resistance using the digital droplet polymerase chain reaction (ddPCR) approach to examine plasma ctDNA Utilizing the Statistical Package for the Social Sciences, statistical tests were used to examine the data (SPSS). The data were analyzed by statistical tests using the Statistical Package for the Social Sciences (SPSS). Results: A total of 31 patients were recruited as study participants. The majority of the research subjects were female (64.5%), aged 20-69 years old (58%), and non-smokers (67.7%). Exon 19 deletions were the most prevalent EGFR mutation (58.1%). The incidence of acquired resistance was found in 10 subjects (32.3%). Patients with acquired resistance were predominately female (70%), non-smokers (80%), and with gefitinib therapy (90%). The average time for EGFR-TKI treatment until acquired resistance occurred was 12.6 months. Conclusion: The incidence of acquired resistance was mainly found in women without a smoking history after 12.6 months of treatment with EGFR-TKI.